PELATIHAN PEMBUKUAN SEDERHANA DAN PERHITUNGAN HARGA JUAL UNTUK KELOMPOK INDUSTRI KAKAO DESA WOLONWALU - Eugenius Besli; Maria Florentina Rumba; Gregoriany cesilia Krisphina Dessy Dasilva; Maximus Gepa (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2023)
Cocoa plants have become one of the superior crops in Sikka Regency. Recognizing this potential, Industri Kakao group took the initiative to process cocoa beans into powder so that it has added value. During the business operation, the group has encountered problems related to the accounting process. Industri Kakao group of Wolonwalu Village has two main accounting problems. First, the recording of transactions is not based on valid transaction evidence and the bookkeeping is not systematic. This also leads to the group never producing profit and loss reports. Second, the determination of selling prices is only based on the cost of raw materials and ignores other costs. Training is provided to address the two problems experienced by the Cocoa Industry Group. The training method uses a lecture approach and practical exercises using Ms. Excel. Industri Kakao group acknowledges that the training provided is targeted and desires ongoing mentoring by the team.